PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO, CURRENT RATIO, DAN VOLUME PERDAGANGAN SAHAM TERHADAP NILAI PERUSAHAAN PADA EMITEN PERTAMBANGAN DI BURSA EFEK INDONESIA PERIODE 2011-2013 - MARJANI AMILIYAH (Jurnal Manajerial, 2018)
ABSTRACTThe value of the company is the company's performance which is reflected in the stock price determined by the supply and demand in the capital market which reflects the public's assessment of the company's performance. The purpose of this study is to examine the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR) and stock trading volume on the value of the company both partially and simultaneously in mining companies listed on the Stock Exchange for the period 2011-2013 . The data used in this study are the financial statements of each company published on the website www.idx.co.id. The population in this study were 40 mining companies listed on the Stock Exchange in 2013. The sampling method used in this study was purposive sampling method so that the samples obtained were 18 mining companies. The variables used in this study are ROE, DER, CR, stock trading volume and PBV. The analysis technique used is multiple regression analysis and hypothesis testing using partial t-test, simultaneous F test with a significance level of 5%. The results of the study prove that partial Return on Equity (ROE) and Debt to Equity Ratio (DER) significantly affect the value of Frim while Current Ratio (CR) and stock trading volume do not significantly influence the value of the Company. and also simultaneously Return on Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR) and stock trading volume significantly influence the value of the Company in mining companies listed on the Stock Exchange in 2011-2013